2014
DOI: 10.1021/jp5060099
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insight into the Coordination of Cyclic β-d-Glucose to [Al(OH)(aq)]2+ and [Al(OH)2(aq)]1+ Ions

Abstract: The coordination of cyclic β-D-glucose (CDG) to both [Al(OH)(aq)](2+) and [Al(OH)2(aq)](1+) ions has been theoretically investigated, using quantum chemical calculations at the PBE0/6-311++G(d,p), aug-cc-pvtz level under polarizable continuum model IEF-PCM, and molecular dynamics simulations. [Al(OH)(aq)](2+) ion prefers to form both six- and five-coordination complexes, and [Al(OH)2(aq)](+) ion to form four-coordination complex. The two kinds of oxygen atoms (on hydroxyl and ring) of CDG can coordinate to bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 51 publications
3
37
0
Order By: Relevance
“…Determination of the Active Species. In our previous computational work, 39 it was found that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 reaction conditions, ESI-MS/MS methods were used. As shown in Figure S2, 40 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 In order to confirm whether [Al(OH)2(aq)] + species was responsible for the isomerization, HCl was added to suppress the hydrolysis of Al 3+ , which will decrease the concentration of [Al(OH)2(aq)] + species in the reaction mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…Determination of the Active Species. In our previous computational work, 39 it was found that 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 reaction conditions, ESI-MS/MS methods were used. As shown in Figure S2, 40 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 In order to confirm whether [Al(OH)2(aq)] + species was responsible for the isomerization, HCl was added to suppress the hydrolysis of Al 3+ , which will decrease the concentration of [Al(OH)2(aq)] + species in the reaction mixtures.…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of Lewis acid catalyst (AlCl 3 ), the yield of HMF was 46%, and near absolute conversion of glucose was achieved in the system, observing the occurrence of fructose. In previous reports3132, it was found that the main active species in glucose-to-fructose isomerization reaction was most possibly the hydrolyzed aluminum species [Al(OH) 2 (aq)] + . Combined with Lewis acid and Brønsted acid, HMF yield was increased to 54.5%, and this improvement might be attributable to decreased pH (pH = 3.37 to pH = 2.50).…”
Section: Resultsmentioning
confidence: 99%
“…[17] This indicates that the hydrolyzedA ls pecies and Pd(OAc) 2 werem ore active than HCl and Pd(OAc) 2 for the one-pot catalytic deoxygenation of fructose. [18] Additionally,t he yields of furfural and FA increased if the amount of HCl was increased, which demonstratest he ease of fructose decomposition in the presence of al arge amount of Brønsted acid. [13] We tried to removet he water that existed in the solvent and was formed during the dehydration step by adding 4 molecular sieves.…”
Section: Effect Of Water On the One-pot Reactionmentioning
confidence: 87%